2000
DOI: 10.1111/1467-8624.00183
|View full text |Cite
|
Sign up to set email alerts
|

Parenting among Low‐Income, African American Single Mothers with Preschool‐Age Children: Patterns, Predictors, and Developmental Correlates

Abstract: Dimensions and patterns of parenting were examined in a sample of 193 low-income African American single mothers with preschool-age children. Factor analyses yielded three dimensions: Aggravation, Nurturance, and Cognitive Stimulation. Cluster analysis yielded four patterns of parenting: Aggravated but Nurturant; Cognitively Stimulating; Patient and Nurturant; and Low Nurturance. Discriminant function analysis was used to predict membership in each of the four parenting clusters. Two composite functions emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
115
1
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 59 publications
17
115
1
5
Order By: Relevance
“…The first and most frequently employed assessment of parenting strategies, the AAPI-2, was not a significant predictor of social-emotional problems in African-American toddlers. This finding contrast with previous research linking higher levels of involved parenting strategies with fewer behavior problems in older African-American children (Jackson et aI., 2000;McGroder, 2000). A possible explanation for this finding is that parent responses for the AAPI-2 subscales in this study were found to be in the low to moderate category: parental empathy towards children -3.53; expectation of children -4.01; parent-child family roles -4.16; use of corporal punishment -3.73; children's power and independence -4.47.…”
Section: Parenting Strategies In African-american Caregivers Of Toddlerscontrasting
confidence: 99%
See 4 more Smart Citations
“…The first and most frequently employed assessment of parenting strategies, the AAPI-2, was not a significant predictor of social-emotional problems in African-American toddlers. This finding contrast with previous research linking higher levels of involved parenting strategies with fewer behavior problems in older African-American children (Jackson et aI., 2000;McGroder, 2000). A possible explanation for this finding is that parent responses for the AAPI-2 subscales in this study were found to be in the low to moderate category: parental empathy towards children -3.53; expectation of children -4.01; parent-child family roles -4.16; use of corporal punishment -3.73; children's power and independence -4.47.…”
Section: Parenting Strategies In African-american Caregivers Of Toddlerscontrasting
confidence: 99%
“…Parenting strategies were also associated with child behavior and preschool ability. McGroder (2000) reported similar findings when investigating African-American mothers with preschoolers from low socioeconomic families. McGroder concluded that there was a positive relationship between maternal nurturance related to parenting support and control and the children's social maturity at the child's entry to school.…”
Section: Parenting Support and Control In African-american Familiessupporting
confidence: 58%
See 3 more Smart Citations